Housing demand shocks and households' balance sheets - Marc Anderes (ETH Zurich, KOF Swiss Economic Institute, 2021)
We examine the dynamic effects of housing demand shocks on a large set of U.S. macroeconomic series and detailed household balance sheet components for four wealth percentile groups. The results show that a positive housing shock translates into a large and persistent boom of economic activity, an expansion of credit and an increase of interest rates. While households of all wealth percentile groups make heavy use of home equity-based borrowing, we find a larger consumer spending sensitivity for weaker balance sheet households. This is supported by the elasticities of consumption with respect to house prices implied by our structural dynamic factor model. A historical decomposition suggests that housing demand shocks have largely contributed to the pronounced drop in poorer households' consumption during the Great Recession. Variance decompositions indicate that the identified housing shock has high explanatory power for key economic indicators, housing indices and household balance sheet series.
hdl:20.500.11850/470105
Keywords: D31; E21; E32; E44; R31; 330; Housing demand shocks; Household balance sheets; Bayesian dynamic factor model